Rationality, practice variation and person‐centred health policy: a threshold hypothesis. Issue 6 (7th December 2015) - Djulbegovic, Benjamin; Hamm, Robert M.; Mayrhofer, Thomas; Hozo, Iztok; Van den Ende, Jef
Abstract: Variation in practice of medicine is one of the major health policy issues of today. Ultimately, it is related to physicians' decision making. Similar patients with similar likelihood of having disease are often managed by different doctors differently: some doctors may elect to observe the patient, others decide to act based on diagnostic testing and yet others may elect to treat without testing. We explain these differences in practice by differences in disease probability thresholds at which physicians decide to act: contextual social and clinical factors and emotions such as regret affect the threshold by influencing the way doctors integrate objective data related to treatment and testing. However, depending on a theoretical construct each of the physician's behaviour can be considered rational. In fact, we showed that the current regulatory policies lead to predictably low thresholds for most decisions in contemporary practice. As a result, we may expect continuing motivation for overuse of treatment and diagnostic tests. We argue that rationality should take into account both formal principles of rationality and human intuitions about good decisions along the lines of Rawls' 'reflective equilibrium/considered judgment'. In turn, this can help define a threshold model that is empirically testable.